Influence of affective distractors on working memory capacity in relation to symptoms of posttraumatic stress disorder. Issue 5 (2nd May 2019) - Mirabolfathi, Vida; Moradi, Ali Reza; Jobson, Laura
Summary: Symptoms evoked in individuals with posttraumatic stress disorder (PTSD) when processing trauma‐relevant material arguably impair higher order cognitive functions. An example is working memory capacity (WMC), which has been shown to be disrupted by affective distractors. However, it is unknown whether this association varies across different types of PTSD symptoms. This study explored the association between WMC performed in affective (relative to neutral) contexts in relation to different symptoms of PTSD (avoidance, re‐experiencing, hyperarousal). Motor vehicle accident survivors with PTSD and without PTSD completed a delayed‐match‐to‐sample task including trauma‐related, neutral, and scrambled distractors in the interval between the presentation of the memoranda and the recognition target. The results showed that there was support for an indirect pathway between PTSD diagnosis and WMC performed in affective (versus neutral) contexts through re‐experiencing and avoidance symptoms. The findings suggest that avoidance symptoms in particular may benefit from interventions directed at improving WMC.